2004
DOI: 10.1186/1471-2164-5-83
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species hybridisation of human and bovine orthologous genes on high density cDNA microarrays

Abstract: Background: Cross-species gene-expression comparison is a powerful tool for the discovery of evolutionarily conserved mechanisms and pathways of expression control. The usefulness of cDNA microarrays in this context is that broad areas of homology are compared and hybridization probes are sufficiently large that small inter-species differences in nucleotide sequence would not affect the analytical results. This comparative genomics approach would allow a common set of genes within a specific developmental, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…The number of genes detected as expressed exclusively in the oocyte was rather low [166 (12%)]. This unexpectedly low number of oocyteexpressed genes detected might be due partly to the fact that the comparative sequence homology for the majority of the genes presented as probes on the array is low and thus undetected as expressed with the high stringency of the hybridization protocol previously described (3). In support of this finding is the fact that in our previous studies using the same array platform (4) we detected ϳ6,000 genes expressed in the human blastocyst, whereas only 1,324 were detected as expressed in the bovine blastocyst.…”
Section: Global Data Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…The number of genes detected as expressed exclusively in the oocyte was rather low [166 (12%)]. This unexpectedly low number of oocyteexpressed genes detected might be due partly to the fact that the comparative sequence homology for the majority of the genes presented as probes on the array is low and thus undetected as expressed with the high stringency of the hybridization protocol previously described (3). In support of this finding is the fact that in our previous studies using the same array platform (4) we detected ϳ6,000 genes expressed in the human blastocyst, whereas only 1,324 were detected as expressed in the bovine blastocyst.…”
Section: Global Data Analysismentioning
confidence: 90%
“…This corresponds to four technical replicates for oocytes and blastocysts, respectively. Full details of labeling and hybridization reactions, slide washing (0.2ϫ SSC-0.1% SDS, 55°C), and scanning are described elsewhere (3,4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of gene expression patterns in early embryos using cDNA microarray provides insight into the function of gene regulatory networks leading to unravel the molecular mechanisms underlying developmental abnormalities (Adjaye et al 2004). Therefore, we focused on searching for genes that regulate the developmental competence of embryos to term.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that a large number of genes were differentially expressed, thereby validating the use of cross-species hybridizations for nonhuman primate studies. Adjaye et al [30] used human and bovine fetal brain target samples on a human cDNA microarray.…”
Section: Discussionmentioning
confidence: 99%